Implementation of Deep Learning Strategies to Increase Historical Awareness of Senior High School Students - Desvian Bandarsyah; Jumardi; Andi (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Negeri Jakarta, 2025)
This study analyzes the application of deep learning strategies in Indonesian History classes at three senior high schools of Labschool UHAMKA Jakarta and their contribution to fostering students’ historical consciousness. History education in Indonesia is still predominantly focused on memorization of historical facts such as dates, figures, and event chronologies, which often leads to a superficial and less reflective understanding of history. Therefore, this study aims to explore how deep learning strategies can enhance students' historical consciousness. Using a mixed-methods explanatory sequential design, data were gathered from 50 eleventh-grade social science students through questionnaires, supported by interviews with 12 students and 3 history teachers, and classroom observations. Indicators measured included reflective activities, primary source analysis, real-life relevance, and collaboration, while dimensions of historical consciousness covered chronological understanding, interpretation, continuity, and present relevance. Regression analysis showed a strong, positive, and significant relationship between deep learning strategies and historical consciousness (β = 0.62, p < 0.01). Qualitative findings reinforced these results, highlighting that primary source integration, collaborative projects, reflective discussions, and the use of digital tools such as Padlet and Google Classroom enhanced engagement, comprehension, and connections between the past and present. Teachers reported higher participation and critical dialogue in the classroom. Overall, deep learning strategies proved effective in combining cognitive, affective, and reflective dimensions, enriching history education, and cultivating students as critical, contextual, and socially responsible citizens.